2020
DOI: 10.1002/jmrs.428
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of a deformable image registration quality assurance tool for head and neck cancer patients

Abstract: Introduction A challenge in implementing deformable image registration (DIR) in radiation therapy planning is effectively communicating registration accuracy to the radiation oncologist. This study aimed to evaluate the MIM® quality assurance (QA) tool for rating DIR accuracy. Methods Retrospective DIR was performed on CT images for 35 head and neck cancer patients. The QA tool was used to rate DIR accuracy as good, fair or bad. Thirty registered patient images were ass… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
8
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 15 publications
0
8
0
Order By: Relevance
“…A recent study revealed that, with CT images from 35 head and neck cancer patients, the “Reg Refine” registrations conducted by experienced operators were classified as good, fair and bad, corresponding to STD‐JD values of 0.05, 0.21, and 0.68, respectively. 28 In contrast, the hybrid FEM method automatically updates the MIM registrations in interior regions, reducing STD‐JDs from 0.44 to 0.17 for MIM‐II, from 0.33 to 0.15 for MIM‐CC, and from 0.24 to 0.10 for MIM‐MM. The one‐tailed Wilcoxon‐Mann‐Whitney tests show that these improvements are statistically significant, with all p ‐values less than 0.0084.…”
Section: Discussionmentioning
confidence: 99%
“…A recent study revealed that, with CT images from 35 head and neck cancer patients, the “Reg Refine” registrations conducted by experienced operators were classified as good, fair and bad, corresponding to STD‐JD values of 0.05, 0.21, and 0.68, respectively. 28 In contrast, the hybrid FEM method automatically updates the MIM registrations in interior regions, reducing STD‐JDs from 0.44 to 0.17 for MIM‐II, from 0.33 to 0.15 for MIM‐CC, and from 0.24 to 0.10 for MIM‐MM. The one‐tailed Wilcoxon‐Mann‐Whitney tests show that these improvements are statistically significant, with all p ‐values less than 0.0084.…”
Section: Discussionmentioning
confidence: 99%
“…JD maps were also generated within the MIM software for the ten cases, for both DIR algorithms. The MIM software creates the Jacobian determinant map using the deformation grid, which itself is obtained from the deformed CT created within MIM 16 . The plan ROIs were superimposed upon the JD maps, and the mean and standard deviations of the ROI JD values were calculated.…”
Section: Methodsmentioning
confidence: 99%
“…The MIM software creates the Jacobian determinant map using the deformation grid, which itself is obtained from the deformed CT created within MIM. 16 The plan ROIs were superimposed upon the JD maps, and the mean and standard deviations of the ROI JD values were calculated. Local expansions are characterized by JD > 1,and contractions by 0 < JD < 1; JD = 1 indicates no local volume change.…”
Section: Comparison Of Dose Accumulation Uncertainties For Two Dir Algorithmsmentioning
confidence: 99%
“…To access performance of each method on registering data from different populations and acquired with different protocols and scanners, we also report evaluation metrics of the intra-population subject pairs (i.e., between HCP and HCP, ABCD and ABCD, and PPMI and PPMI) and inter-population subject pairs (i.e., between HCP and ABCD, between HCP and PPMI, and between ABCD and PPMI). In addition, to evaluate the regularity of the 8. http://dti-tk.sourceforge.net/pmwiki/pmwiki.php deformation fields, we compute the Jacobian determinant of the deformation field of each testing image pair (as used in multiple related studies [54], [83], [84]). Specifically, the Jacobian matrix at each voxel captures local properties around the voxel, where a non-positive determinant indicates that the deformation is not diffeomorphic [54], [85].…”
Section: Comparison To State-of-the-art Methodsmentioning
confidence: 99%